PENDUGAAN KELEMBAPAN TANAH DENGAN MENGGUNAKAN METODE SOIL MOISTURE INDEX (SMI) DI KEBUN KOPI BANGELAN, KABUPATEN MALANG, JAWA TIMUR - Almira Harwidya Irenasari; Soemarno Soemarno (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Water is one of the limiting factors in the growth of coffee plants. If plants experience a lack of water, it can inhibit plant growth and, at a critical level, can lead to drought stress and plant damages. The available soil water to plants can be estimated from the level of soil moisture index. The monitoring of soil moisture status can be used in improving the management of coffee plantations. Soil Moisture Index (SMI) is a method that can be used to estimate the level of soil moisture using remote sensing technology using NDVI and LST values. The purpose of this study was to analyze the status and distribution of soil moisture at the coffee plantation; analyze the relationship between vegetation index and soil moisture; and analyzed the relationship between soil moisture status using the SMI method and soil moisture measured in coffee plantations. Results showed that the soil moisture index obtained from Landsat 8 OLI/TIRS image processing had an average value of 0.60. The average soil moisture index at the study site is 1.05. Soil moisture index from the Landsat 8 OLI/TIRS image has a significant positive effect on soil moisture at the study site (y = 7.4996x â€“ 3.4789; R2 = 0.7146**). Â It is suggested that the SMI method can be used to estimate soil moisture in the coffee plantation.